PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID DENGAN MENGGUNAKAN APLIKASI APPY PIE PADA MATA PELAJARAN INSTALASI PENERANGAN LISTRIK - Putri Kanti Wigati; Hamonangan Tambunan (JEVTE Journal of Electrical Vocational Teacher Education, 2023)
Abstract The research aims to determine the feasibility and effectiveness of developing android-based media using the Appy Pie application on the subject of electrical lighting installations. This study uses the Research and Development (R&D) method with the development procedure used referring to the ADDIE model developed by Dick and Carry (1996) which includes analysis, design, development, implementation and evaluation. The subjects of this study were students of class XI TITL SMK N 13 Medan. The feasibility of the developed media refers to media experts with a score of 93% in the "very feasible" category, the feasibility of the material by material experts gets a score of 85% in the "very feasible" category, and 93% obtained through learning practitioners in the "very feasible" category. The product trial results obtained a positive response to the use of media > 65%. The effectiveness of the product from the posttest results obtained a sig.2-tailed value of 0.009 <0.05, meaning that there is a significant difference between the control and experimental classes. From the results of the posttest average, the experimental class obtained 7.9 with an increase in score of 2.1 compared to the control class, which only obtained an average posttest of 7.2. Thus the media developed is effective.Â Key Words: research development, android, Appy PieÂ AbstrakPenelitian ini bertujuan untuk mengetahui kelayakan dan efektivitas pengembangan media berbasis android menggunakan aplikasi Appy Pie pada mata pelajaran instalasi penerangan listrik. Penelitian ini menggunakan metode Research and Development (R&D) dengan prosedur pengembangan yang digunakan mengacu pada model ADDIE yang dikembangkan oleh Dick and Carry (1996) yang meliputi analisis, desain, pengembangan, implementasi dan evaluasi. Subjek penelitian ini adalah siswa kelas XI TITL SMK N 13 Medan. Kelayakan media yang dikembangkan merujuk pada ahli media dengan perolehan nilai 93% dengan kategori â€œsangat layakâ€, kelayakan materi oleh ahli materi memperoleh nilai 85% dengan katogori â€œsangat layakâ€, dan 93% diperoleh melalui praktisi pembelajaran dengan kategori â€œsangat layakâ€. Hasil uji coba produk memproleh respon positif penggunaan media > 65%. Efektivitas produk dari hasil posttest diperoleh nilai sig.2-tailed sebesar 0,009 < 0,05 artinya terdapat perbedaan yang signifikan antara kelas kontrol dan eksperimen. Dari hasil rata-rata posttest kelas ekperimen memperoleh 7,9 dengan peningkatan skor sebesar 2,1 dibandingkan dengan kelas kontrol hanya memperoleh rata-rata posttest sebesar 7,2. Dengan demikian media yang dikembangkan efektif.Â Kata Kunci: Penelitian Pengembangan, Android, Appy Pie